Macrophage‐derived inflammatory cytokines regulate growth factors and pain‐related molecules in mice with intervertebral disc injury. Issue 8 (23rd March 2018) - Miyagi, Masayuki; Uchida, Kentaro; Takano, Shotaro; Fujimaki, Hisako; Aikawa, Jun; Sekiguchi, Hiroyuki; Nagura, Naoshige; Ohtori, Seiji; Inoue, Gen; Takaso, Masashi
ABSTRACT: Upregulation of inflammatory cytokines and various growth factors is a significant contributor to discogenic low back pain. The aim of this study was to investigate possible regulation of pain‐related molecules by macrophages and the role of macrophage‐derived molecules in injured intervertebral disc (IVD)s. C57BL/6J mice were used in this study. We characterized the expression profiles of genes for tumor necrosis factor (TNF)‐alpha, interleukin (IL)‐1beta, nerve growth factor (NGF), and vascular endothelial growth factor (VEGF) in both intact and injured IVDs. We examined whether macrophage depletion, induced by systemic injection of clodronate‐laden liposomes, affected the expression of these molecules in injured IVDs. The effect of TNF‐alpha on cultured F4/80‐CD11b‐cells in injured IVDs was investigated. Expression of TNF‐alpha and IL‐1beta was significantly increased in injured IVDs, but decreased by macrophage depletion. Expression of NGF and VEGF was also significantly increased, but by contrast was not decreased by macrophage depletion. TNF‐alpha treatment of F4/80‐cells from injured IVDs upregulated NGF, VEGF, cyclooxygenase (COX)‐2, and microsomal prostaglandin E synthase‐1 (mPGES1). IVD injury upregulated inflammatory cytokines and various growth factors. Macrophages in the injured IVDs produced inflammatory cytokines, but not growth factors. Macrophage‐derived inflammatory cytokines regulate growth factors and pain‐related molecules. These findings demonstrate further complexity in the pathogenesis of discogenic pain. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2274–2279, 2018.